2021
DOI: 10.3390/cancers13122932
|View full text |Cite
|
Sign up to set email alerts
|

TGF Beta Induces Vitamin D Receptor and Modulates Mitochondrial Activity of Human Pancreatic Cancer Cells

Abstract: The inflammatory cytokine TGFβ is both a tumor suppressor during cancer initiation and a promoter of metastasis along cancer progression. Inflammation and cancer are strictly linked, and cancer onset often correlates with the insufficiency of vitamin D, known for its anti-inflammatory properties. In this study, we investigated the interplay between TGFβ and vitamin D in two models of human pancreatic cancer, and we analyzed the metabolic effects of a prolonged TGFβ treatment mimicking the inflammatory environm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 63 publications
0
6
0
Order By: Relevance
“…The results revealed that ARPE-19 cells did not express detectable basal levels of VDR since the signal corresponding to the receptor was not visible in the untreated cells (ctrl, C). However, the amount of protein was, unsurprisingly, greatly enhanced by the treatment with TGF-β since this induction has been previously described [ 52 ]. In contrast, VDR expression was not induced by SF treatment, neither at 1 µM nor 10 µM.…”
Section: Resultsmentioning
confidence: 75%
“…The results revealed that ARPE-19 cells did not express detectable basal levels of VDR since the signal corresponding to the receptor was not visible in the untreated cells (ctrl, C). However, the amount of protein was, unsurprisingly, greatly enhanced by the treatment with TGF-β since this induction has been previously described [ 52 ]. In contrast, VDR expression was not induced by SF treatment, neither at 1 µM nor 10 µM.…”
Section: Resultsmentioning
confidence: 75%
“…Figure 3 shows that purified GOS, fermented product and butyrate induced the transcription of the respiratory complex and ATP synthase, whereas permeate was less effective. In this experimental set, the treatment with TGF-β was considered a positive control since the cytokine is a respiratory modulator [ 45 ]. Next, we wondered if any factor, and if so, which, could modulate the mitochondrial metabolism in response to GOS stimulation.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, 1,25(OH) 2 D 3 reduces fibroblast differentiation and ECM formation via Smad2/3-dependent TGF-β1 signaling pathways [ 201 ] and the activation of VDR signals suppressed TGFβ-mediated EMT in a model of renal fibrosis [ 202 ]. Fiz et al [ 203 ] found that TGFβ/vitamin D interplay positively modulates mitochondrial activity in human pancreatic cancer cells. It was documented that activated VDR inhibits EMT through the modified epithelial mitochondrial function during the process of fibrosis [ 204 ].…”
Section: Senotherapeuticsmentioning
confidence: 99%